PROSES BIOSORPSI CU DAN PHENOL DALAM KONDISI TUNGGAL MAUPUN SIMULTAN DENGAN MENGGUNAKAN LUMPUR AKTIF KERING - Yunus Fransiscus (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
The application of dried activated sludge as a biosorbent for copper and phenol was studied. From a series of batch experiment for single component, it was determined the sorption capacity of biosorbent are 29 mg/L and 98 mg/L for copper and phenol respectively. Sorption isotherm showed that these two adsorbates have different sorption mechanism. copper was able to form a more complete monolayer, while phenol tend to form a multilayer reaction. In simultaneous experiments it was concluded that phenol was more dominant than copper. The sorption capacity of biosorbent for copper decreased gradually as the increasing of phenol concentration. This condition was not reversible, sorption capacity of biosorbent for phenol was more stable. eventhough copper concentration was increased.